Jurisdiction of IP-Court: Issues of Theory and Practice (Law and Safety, 2020)
The author of the article studies the current state of determining the jurisdiction of the IP-court in Ukraine. The emphasis is placed on the relevance of this scientific article due to the current state of the formation of the IP-court and its composition.The principles of the judicial system of Ukraine, which are territoriality, specialization and instance, are determined. Specific features of each of the principles of the judicial system of Ukraine are indicated.The author’s vision of the category of "jurisdiction of the IP-court" is suggested. That category is a set of powers of the IP-court to resolve certain categories of legal disputes and cases in the field of intellectual property.It is emphasized that the principle of territoriality of the IP-court in Ukraine extends its jurisdiction to the entire territory of the state, which is established by the Basic Law and the title law on the judiciary and the status of judges. Accordingly, the principle of territoriality must be consistent and organically combined with the principle of specialization.The powers of the IP-court have been established. They have been offered to be defined in the title law on the Supreme Court on intellectual property issues. Perspective directions of further scientific research are defined, namely: legal bases of activity of the IP-court in Ukraine and a place of the norms of administrative legislation among them.It is concluded that the degree of efficiency of the IP-court in Ukraine depends on the definition of all these components of jurisdiction, which is currently the key one at the initial stage of the formation of its legal base. The definition of each principle creates the conditions for the operation of the second principle, which makes it impossible for them to function independently. However, each of the principles of the judicial system plays an independent role in its construction and they all together contribute to the effective organization and legal functioning of the judicial system in general, and the activities of the IP-court in particular.
Keywords: court; IP-court; jurisdiction; powers; competence; principle; territoriality; specialization; instance